Lateral Gene Transfer Acts As an Evolutionary Shortcut to Efficient C4 Biochemistry. (10th June 2020) - Phansopa, Chatchawal; Dunning, Luke T; Reid, James D; Christin, Pascal-Antoine
Abstract: The adaptation of proteins for novel functions often requires changes in their kinetics via amino acid replacement. This process can require multiple mutations, and therefore extended periods of selection. The transfer of genes among distinct species might speed up the process, by providing proteins already adapted for the novel function. However, this hypothesis remains untested in multicellular eukaryotes. The grass Alloteropsis is an ideal system to test this hypothesis due to its diversity of genes encoding phosphoenolpyruvate carboxylase, an enzyme that catalyzes one of the key reactions in the C4 pathway. Different accessions of Alloteropsis either use native isoforms relatively recently co-opted from other functions or isoforms that were laterally acquired from distantly related species that evolved the C4 trait much earlier. By comparing the enzyme kinetics, we show that native isoforms with few amino acid replacements have substrate K M values similar to the non-C4 ancestral form, but exhibit marked increases in catalytic efficiency. The co-option of native isoforms was therefore followed by rapid catalytic improvements, which appear to rely on standing genetic variation observed within one species. Native C4 isoforms with more amino acid replacements exhibit additional changes in affinities, suggesting that the initial catalytic improvements are followed by gradual modifications. Finally, laterally acquired genes show both strong increases in catalytic efficiency and important changes in substrate handling. We conclude that the transfer of genes among distant species sharing the same physiological novelty creates an evolutionary shortcut toward more efficient enzymes, effectively accelerating evolution.